Global Epidemiology of Chronic Venous Disease: A Systematic Review With Pooled Prevalence Analysis. Issue 6 (December 2021) - Salim, Safa; Machin, Matthew; Patterson, Benjamin O.; Onida, Sarah; Davies, Alun H.
Abstract : Objective: To provide an updated estimate of the global prevalence of CVD and to comprehensively evaluate risk factors associated with this condition. Background: CVD is an important cause of morbidity internationally, but the global burden of this condition is poorly characterized. The burden of CVD must be better characterized to optimize service provision and permit workforce planning to care for patients with different stages of CVD. Methods: A systematic search in Ovid MEDLINE and Embase (1946–2019) identified 1271 articles. Full-text, English language articles reporting on the epidemiology of CVD in a general adult population were included. Data extraction was performed by 2 independent reviewers, in accordance with a preregistered protocol (PROSPERO: CRD42019153656). STATA and Review Manager were used for quantitative analysis. A crude, unadjusted pooled prevalence was calculated for each Clinical (C) stage in the Clinical, Etiologic, Anatomic, Pathophysiologic classification and across different geographical regions. Qualitative analysis was performed to evaluate associated risk factors in CVD. Results: Thirty-two articles across 6 continents were identified. Nineteen studies were included in the overall pooled prevalence for each Clinical (C) stage; pooled estimates were: C0 s: 9%, C1: 26%, C2: 19%, C3: 8%, C4: 4%, C5: 1%, C6: 0.42%. The prevalence of C2 disease was highest in Western Europe and lowest in the Middle East and Africa. Commonly reported risk factors for CVD included: female sex (OR 2.26, 95% confidence intervals 2.16–2.36, P < 0.001), increasing age, obesity, prolonged standing, positive family history, parity, and Caucasian ethnicity. There was significant heterogeneity across the included studies. Conclusions: CVD affects a significant proportion of the population globally; however, there is significant heterogeneity in existing epidemiological studies. Abstract : Supplemental Digital Content is available in the text